2014
DOI: 10.1002/rcm.6813
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles of 20(S )-protopanaxadiol in rats after oral administration using ultra-performance liquid chromatography/quadrupole time-of-flight tandem mass spectrometry

Abstract: The results showed that phase I metabolites are monooxygenation, dioxygenation and oxidative dehydrogenation metabolites, and phase II metabolic pathways were demonstrated to be cysteine conjugation and glucuronidation. The newly identified metabolites are useful to understand the mechanism of elimination of PPD and, in turn, its effectiveness and toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The study of PPD metabolism in rats indicated that PPD underwent monooxygenation, deoxygenation, dehydrogenation, cysteine conjugation, and glucuronidation [6]. Small amount of PPD was found in rat plasma, whereas monooxygenated and deoxygenated derivatives represented major circulating metabolites [7]. However, because of the species differences, the metabolic profile of most drugs in humans and rodent animals are not comparable.…”
Section: Introductionmentioning
confidence: 99%
“…The study of PPD metabolism in rats indicated that PPD underwent monooxygenation, deoxygenation, dehydrogenation, cysteine conjugation, and glucuronidation [6]. Small amount of PPD was found in rat plasma, whereas monooxygenated and deoxygenated derivatives represented major circulating metabolites [7]. However, because of the species differences, the metabolic profile of most drugs in humans and rodent animals are not comparable.…”
Section: Introductionmentioning
confidence: 99%
“…A new metabolite designated as PPDG (glucuronidation metabolite of PPD) was eluted at 16.48 min by ultra-performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UPLC-Q/TOF-MS) when PPD was incubated with pooled HLMs or RLMs in the presence of Uridine 5′-diphosphoglucuronic acid trisodium salt (UDPGA) ( Figure 1 B). The negative ion mode was used for structure identification because it is more sensitive than positive ion mode for PPD and its metabolite [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Identification of metabolite was carried out on ultra-performance liquid chromatography quadrupole time-of-flight tandem mass spectrometry (UPLC-Q/TOF-MS) (Waters Corporation, Milford, MA, USA) as described in detail previously [ 15 , 31 ]. The peak at RT (retention time) 19.30 min was detected as PPD by Q/TOF-MS analysis ( Figure 1 B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, identification of metabolites, especially reactive metabolites, is still a challenge because of the low concentration and the complexity of biological matrices. In recent decades, liquid chromatography coupled with high‐resolution mass spectrometry, such as Q/TOF‐MS and Q/orbitrap‐MS, has emerged as a powerful and reliable tool for characterizing metabolites . The corresponding data analysis software such as MetaboLynx and Metworks can automatically produce a list of proposed metabolites by a comparative analysis between drug‐containing samples and blank samples based on the mass defect filter (MDF) function, which facilitates metabolite characterization.…”
Section: Introductionmentioning
confidence: 99%